2020
DOI: 10.1111/een.12952
|View full text |Cite
|
Sign up to set email alerts
|

Strong impacts of smoke polluted air demonstrated on the flight behaviour of the painted lady butterfly (Vanessa cardui L.)

Abstract: 1. A major component of biomass burning smoke is fine particulate matter (PM 2.5), which has been shown to generate impacts on insect population dynamics and development. However, little is known about its effect on insect flight behaviour, even though this will influence insect dispersal and distribution, and potentially migration and ecosystem services such as pollination. 2. Here we use a tethered flight mill setup to examine the behaviour of adult painted lady butterflies (Vanessa cardui L.) flying in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Wildfire smoke can also trigger shifts in animal behavior, including movement and vocalization. Such behavioral changes could be due to underlying health effects (Erb et al 2018) or serve to limit exposure to airborne toxins (Singer et al 1989, Dickinson et al 2009, Liu et al 2021b. Some species rely on smoke as an early-warning signal that helps them to avoid wildfires (Engstrom 2010, Höcherl and Tautz 2015, Álvarez-Ruiz et al 2021) or prepare to conserve energy in a post-fire landscape (Geiser et al 2018), whereas others use smoke as a cue to navigate toward newly available resources in burned habitats (Schütz et al 1999, Klocke et al 2011, Milberg et al 2015.…”
Section: Behavioral Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfire smoke can also trigger shifts in animal behavior, including movement and vocalization. Such behavioral changes could be due to underlying health effects (Erb et al 2018) or serve to limit exposure to airborne toxins (Singer et al 1989, Dickinson et al 2009, Liu et al 2021b. Some species rely on smoke as an early-warning signal that helps them to avoid wildfires (Engstrom 2010, Höcherl and Tautz 2015, Álvarez-Ruiz et al 2021) or prepare to conserve energy in a post-fire landscape (Geiser et al 2018), whereas others use smoke as a cue to navigate toward newly available resources in burned habitats (Schütz et al 1999, Klocke et al 2011, Milberg et al 2015.…”
Section: Behavioral Responsesmentioning
confidence: 99%
“…However, some insects, such as the Cape honeybee (Apis mellifera capensis), may not attempt to evade fire and instead use smoke as a cue to retreat to protective nest structures, (Tribe et al 2017). Regardless of their fire avoidance strategy, smoke could compromise the ability of insects to escape fires by impairing flight performance (Liu et al 2021b). Liu et al (2021b) found that the duration, distance, and speed flown by painted lady butterflies (Vanessa cardui L.) decreased following exposure to smoke, which could adversely impact other insect behaviors as well, such as foraging and migration (Liu et al 2021b).…”
Section: Use Of Smoke As a Cue 621 Fire Avoidance Behaviorsmentioning
confidence: 99%
“…However, plastic expressions of various acts of dispersal can be challenging to study by behavioral ecologists, despite dispersal occurring ubiquitously across many biological systems. Dispersal ability, the potential for movement by animals between locations [32], is a fundamental trait for determining geographic range and gene flow within and between populations [24] and it can be dampened [33,34] or induced by persistent deleterious changes in habitat conditions, particularly for philopatric organisms [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, plastic expressions of various acts of dispersal can be challenging to study by behavioral ecologists, despite dispersal occurring ubiquitously across many biological systems. Dispersal ability, the potential for movement by animals between locations [32], is a fundamental trait for determining geographic range and gene flow within and between populations [24] and it can be dampened [33,34] or induced by persistent deleterious changes in habitat conditions, particularly for philopatric organisms [35]. Individuals also display various dispersal characteristics, such as endurance, periodicity, and speed, and these traits have been linked to morphological traits like sex [36], body size [37,38], and wing size [39] as well as trade-offs with reproduction[40].…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on LFS and some indoor biomass burning, since the composition of smoke from indoor sources, such as indoor fuelwood burning and incense sticks, is relatively similar to the smoke components from landscape fires ( Jetter et al 2002 , Lin et al 2008 , See and Balasubramanian 2011 ). For instance, in some laboratory work to observe insect response to smoke, smoke emitted from incense coils is used to simulate the haze from forest fires ( Tan et al 2018 , Liu et al 2021 ). Anthropogenic burning sources such as industrial coal fire, domestic fossil fuel combustion, and traffic engine combustion, were not considered because these commonly occur in anthropogenic settings according to the classification from De Gouw et al (2004) .…”
mentioning
confidence: 99%